RITUAL ADAT LETA URANG SEBAGAI WUJUD KEARIFAN LOKAL MASYARAKAT LAMAHOLOT DAN IMPLIKASINYA BAGI PENDIDIKAN DASAR - Herolima Lasa Kelen; Hiwa Wonda (STKIP Subang, 2025)
ABSTRAKThe Leta Urang traditional ritual is a cultural tradition of the Lamaholot communityin Patisirawalang Village, East Flores Regency, which is performed as a request forrain during prolonged dry seasons. This study aims to describe the symbolicmeanings of the Leta Urang ritual and examine the implications of its values forelementary education. This research employed a qualitative approach usingethnographic methods. Data were collected through participant observation, in-depth interviews with traditional leaders and community members, anddocumentation. Data analysis was conducted through data reduction, data display,and conclusion drawing, supported by source and technique triangulation. Thefindings reveal that the Leta Urang ritual embodies values of religiosity, socialsolidarity, ecological awareness, and collective responsibility toward nature. Thesevalues are relevant to be integrated into elementary school learning to strengthencharacter education, contextual learning based on local culture, and cultural literacy.This study recommends utilizing local wisdom as a contextual learning resource tosupport character development in elementary education.